Who really cares about the environment? CEOs' military service experience and firms' investment in environmental protection. (15th October 2020) - Gao, Yongqiang; Wang, Yingli; Zhang, Miaohan
Abstract: Prior literature suggests that the chief executive officer (CEO) plays a significant role in a firm's environmental performance or voluntary pro‐environmental behaviors; we extend this line of research to examine the effect of CEOs' military service experience on firms' investment in environmental protection. Drawing upon the insights of imprinting theory, we argue that military service experience may instill in CEOs pro‐environmental values such as duty, self‐discipline, self‐sacrifice, and sense of community, which motivate them to adopt pro‐environmental behaviors such as investing more resources in environmental protection. However, we argue that the effects of pro‐environmental values imprinted on CEOs through military service are likely to vary across regions. In regions where the market is more developed and the local value system has experienced greater exposure to the impact of foreign values, and in regions where firms are more concerned about profit, this effect is likely to be attenuated. An analysis of three waves of a nationwide survey of private firms in China using the Tobit regression model supports these predictions. This study makes a unique contribution to the existing literature by linking a firm's pro‐environmental behaviors (i.e., environmental protection investment) to its CEO's experiences in early life (i.e., military service experience).